ASSESSING THE PREVALENCE OF MALARIA AND THE USE OF INSECTICIDE TREATED BED NETS IN GHANA - Saaka, M.; Glover, K. (UDS International Journal of Development, 2017)
Malaria remains a major killer disease in Ghana. Enough evidence abounds that Insecticide treated bed nets (ITN) prevent malaria infections. The use of ITNs seems practical and cheap for the prevention of malaria. Yet the burden of disease is still enormous. The aims of this study were to assess the prevalence of malaria, ascertain the level of ITN ownership and use, as well as factors that hinder ITN use in the two communities of Buipe and Savelugu in the Northern Region of Ghana. A comparative cross-sectional study in which a questionnaire was administered in the two districts in the Northern Region of Ghana (Savelugu/Nanton and Central Gonja Districts) was used. Three hundred and eighty-five respondents (219 females and 166 males) with ages ranging from 6 to over 60 years were questioned on consent (mostly randomly, but a few students too, purposefully at school), with the help of two field workers. The data was analysed using SPSS package version 20. Only 2% of respondents report condemnation of use of ITNs by peers, even though both malaria prevalence and ITN non-use are high. In both research communities, our findings suggest high prevalence of malaria, high levels of awareness about the essence of people sleeping under ITNs (although this can still be improved); and that non-use of ITNs is associated with weather conditions.Â